Subchondral trabecular structural changes in the proximal tibia in an ovine model of increased bone turnover - Holland, J C (Blackwell Science Inc, 2011)
Ovariectomized (OVX) sheep are now considered to be useful models for a variety of metabolic bone disorders. The specific aim of this study was to determine the effects of ovariectomy on the structural parameters and material density of the subchondral bone of the ovine tibial plateau as measured by microcomputed tomography (MicroCT). Twenty-three sheep were examined in this study; 10 of the sheep underwent ovariectomy (OVX), and the remainder (n = 13) were kept as controls (CON). These animals were then sacrificed at 12 months post-operatively. Three-dimensional analyses were performed of osteochondral samples (15 mm deep) which were obtained from the medial tibial plateau using MicroCT. Bone volume fraction of the subchondral trabecular bone was reduced in the ovariectomized sheep as compared to control animals (0.439 vs. 0.483, P = 0.038). Trabeculae were also significantly thinner in the OVX group (0.220 vs. 0.252 mm, P = 0.010), with reduced connectivity density (7.947 vs. 11.524 mm(−3), P = 0.014). There was a trend towards lower numbers of individual trabeculae present in the OVX group as compared to controls, but this did not reach significance (2.817 vs. 3.288 mm(−1), P = 0.1). There was also increased trabecular separation in the OVX group, which again fell short of significance (0.426 vs. 0.387 mm, P = 0.251). There was no difference in hydroxyapatite concentration (HA) between the two groups (929 vs. 932 mgHA cm(−3), P = 0.687). In conclusion, significant alterations of the trabecular architecture under the tibial plateau were observed following 12 months of oestrogen-deficiency in this ovine model. Despite these marked morphological and structural density differences, the material densities were equal in the two groups.